The Influence of Coal Prices, World Oil Prices, Rupiah Exchange Rate, and the 2020 Mineral and Coal Law (Minerba Law) Policy on the Stock Returns of Coal Mining Issuers on the Indonesia Stock Exchange (2015–2025) - Gusti Bagus Putra Cahyana; Riyan Hariyadi; Nicko Albart (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of coal prices, global oil prices, the Rupiah exchange rate, and the implementation of the 2020 Mineral and Coal Law (Minerba Law) on the stock returns of coal mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2015–2025. Using a quantitative approach and secondary data from financial reports, commodity markets, and macroeconomic indicators, this research employs multiple regression analysis to determine the significance and magnitude of each variable's impact on stock returns. The findings are expected to provide insights for investors, policymakers, and industry stakeholders regarding the sensitivity of coal mining stocks to global commodity price fluctuations, exchange rate volatility, and regulatory interventions. The results also aim to contribute to the literature on financial market behavior in the context of developing economies with resource-based industries.